Respuestas

2012-04-28T01:23:54+02:00

Se cumple que:

 

\begin{gathered} \left( {a + 1} \right)^2 \geqslant 0 \hfill \\ \Rightarrow a^2 + 2a + 1 \geqslant 0 \hfill \\ \Rightarrow a^2 + 1 \geqslant - 2a \hfill \\ \Rightarrow a + \frac{1} {a} \geqslant - 2 \hfill \\ \end{gathered} 

 

Para el otro caso, es casi lo mismo, solamente notar que:

 

\begin{gathered} \left( {a - 1} \right)^2 \geqslant 0 \hfill \\ \Rightarrow a^2 - 2a + 1 \geqslant 0 \hfill \\ \Rightarrow a^2 + 1 \geqslant 2a \hfill \\ \Rightarrow a + \frac{1} {a} \geqslant 2 \hfill \\ \end{gathered}

 

Saludos!